Charged particle kinetics and gas heating in CO2 microwave plasma contraction: comparisons of simulations and experiments. (1st May 2022) - Vialetto, L; van de Steeg, A W; Viegas, P; Longo, S; van Rooij, G J; van de Sanden, M C M; van Dijk, J; Diomede, P
Abstract: This work investigates kinetics and transport of CO2 microwave plasmas through simulation results from a 1D radial fluid model and experiments. Simulation results are validated against spatially resolved measurements of neutral species mole fractions, gas temperature, electron number density and temperature obtained by means of Thomson and Raman scattering diagnostics, yielding good agreement. As such, the model is used to complement experiments and assess the main chemical reactions, mass and energy transport in diffuse and contracted plasma regimes. From model results, it is found that, as pressure is raised, the inhomogeneous gas heating induces significant gradients in neutral and charged species mole fractions profiles. Moreover, the transition from diffuse to contracted plasma is accompanied by a change in the dominant charged species, which favours electron–ion recombination over dissociative attachment. Associative ionization rates increase in the plasma core from diffuse to contracted regime. These processes contribute to the increase in the peak electron number density with pressure, that determines radial plasma contraction.